Solve \( 5 t^{2}+13 t+6=0 \) by factoring. Enter your answers as a list separated by a comma \( t= \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
To solve the equation \( 5t^{2} + 13t + 6 = 0 \) by factoring, we look for two numbers that multiply to \( 5 \times 6 = 30 \) and add to \( 13 \). The numbers \( 3 \) and \( 10 \) fit this requirement. Next, we can rewrite the equation by splitting the middle term: \[ 5t^{2} + 3t + 10t + 6 = 0 \] Now group the terms: \[ (5t^{2} + 3t) + (10t + 6) = 0 \] Factor out the common factors: \[ t(5t + 3) + 2(5t + 3) = 0 \] Now, factor by grouping: \[ (5t + 3)(t + 2) = 0 \] Setting each factor equal to zero gives us the solutions: 1. \( 5t + 3 = 0 \) → \( 5t = -3 \) → \( t = -\frac{3}{5} \) 2. \( t + 2 = 0 \) → \( t = -2 \) Therefore, the final answers are: \( t = -\frac{3}{5}, -2 \)